Maneuverable unmanned aerial vehicle "rudder - drive” system design for aeroelastic stability - V. N. Akimov; D. N. Ivanov; A. Yu. Nagornov; S. G. Parafes (Научный вестник МГТУ ГА)
The article considers the technique of designing a "rudder - drive" system aimed at ensuring safety from flutter of the flight control that is the aerodynamic rudder and the "rudder-drive" system stability. The rudder flutter represents a dynamic form of aeroelastic stability loss; the potential possibility of oscillation onset in the "rudder - drive" system is associated with the aeroelastic interaction of the control surface and drive in flight. The implementation of these requirements when designing a maneuverable unmanned aerial vehicle (UAV) is an important condition for the UAV creation that is safe from aeroelastic phenomena. An important stage of designing the aeroelastic "rudder - drive" system is the coordinated choice of the subsystems parameters: a rudder and a drive meeting the requirement of the designed system stability. To solve this problem, an iterative method based on the use of the linearized or nonlinear models of the "rudder-drive" system stability research developed by the authors is proposed. According to this method, the problem solution of the rudder - drive subsystems parameters coordination supposes several stages. Initially the analysis of the "rudder - drive" system stability is carried out. In case of its instability (or lack of necessary stability reserves), the effective measures to ensure the designed system stability are developed. Depending on the selected measures the new tasks of designing the rudder-drive subsystems where the limits imposed by the requirement of the system stability are additionally taken into account. Presenting the methodology basics of designing the aeroelastic "rudder-drive" system is accompanied by the example of coordination of the aerodynamic rudder, the electrical and mechanical type drive parameters in which stability of the aeroelastic system is provided by means of the correction of the rudder design characteristics.